Therapeutic adjuncts in the endoscopic management of urethral stricture disease: past, present, and future - Singh, Jas (Frontiers in Urology, 2024)
Urethral stricture disease is a recurrent and debilitating condition affecting many men of all ages. Management may involve endoscopic or surgical treatment. Surgical urethral reconstruction remains the gold standard treatment and is associated with higher success rates in terms of stricture recurrence free-survival. However, urethroplasty is not available to patients with significant medical comorbidities, or those wishing to forego invasive surgery. Endoscopic treatment is aimed at improving lower urinary tract symptoms and relieving obstruction while maximizing time to stricture recurrence with the aid of therapeutic adjuncts. The aim of this review is to discuss the mechanism of action and role of therapeutic adjuncts and highlight some of the lesser-known adjuncts that have been utilized with success in this space.